Investigation of Palm Weevil Rhynchophorus spp. Infestation on Oil Palm Plantation at Kerincikanan, Siak, Riau - Adi, Hanindyo; Sudaryatno, Sudaryatno; Aldawood, Abdulrahman Saad; Hadisusanto, Suwarno; Sukirno, Sukirno (AGRIVITA Journal of Agricultural Science, 2025)
Rhynchophorus spp. has been observed to be a potential pest in oil palm plantations in Indonesia. Rhynchophorus spp. has been reported to have attacked oil palm in Kalimantan and Papua, but reports regarding attacks by Rhynchophorus spp. in Sumatra have not been updated. Riau is the biggest producer of crude palm oil. This study aims to investigate Rhynchophorus spp. at oil palms in Siak, Riau. The study was conducted in the smallholder area of the Kerincikanan region. The study used survey methods to observe the symptoms of oil palms infested by Rhynchophorus spp. Pheromone aggregate traps were also used to capture Rhynchophorus spp. The results showed that after tree felling, two oil palms were positively infested by Rhynchophorus spp. Both the oil palms exhibited characteristic symptoms, including a collapsing crown, no visible injury or fungal infections in the stem, some leaves were still green, while others were dry. While, other eight oil palms were suspected to be infested by Rhynchoporus spp. Based on morphological characters, it was shown that Rhynchophorus spp. captured was R. vulneratus. These results suggest that oil palm plantations in the studied area should increase their awareness of the palm weevil's attack and implement mitigation approaches to mitigate further impacts.